The Holy Grail of luxury tourism: A holistic bibliometric overview - Lopes, João M. (2022)
This study aims to carry out a comprehensive bibliometric analysis to identify, synthesize and incorporate existing studies on the tourism industry, envisioning and directing future studies and trends in luxury tourism. The study analyses 340 Web of Science scientific articles published between 1993–2022. Four clusters were identified: “Contribution of Luxury Tourism to the development”; “Luxury Shopping in Tourism”; “Demand behaviour in luxury tourism,” and “Digital Transformation in luxury tourism.” Existing publications can be grouped into three phases. In the first phase, luxury tourism was studied from a macro and sectoral perspective; in the second phase, they focused on the behavior of the demand for luxury tourism and in the third phase on the transformation of the luxury tourism industry induced by digital transformation, economic and pandemic crises, demographic changes and guidelines for sustainability. This study resulted in a set of implications for the development of cross-community collaborative luxury tourism, aimed at new target groups of luxury consumers, in harmony with strategies of sustainability, digitalization and well-being of luxury consumers. In addition to being an important tool for policymakers and managers in the luxury tourism industry, it identifies new emerging issues in this sector for academics.